Dynamic changes in macrophage morphology during the progression of choroidal neovascularization in a laser-induced choroidal neovascularization mouse model - Nana Xu; Tao Sun; Yulan Wang; Xiaowei Tong; Shiheng Lu; Fan Yang; Jing Wang; Qiyu Bo; Junran Sun; Xiaodong Sun (BMC Ophthalmology, 2023)
Abstract Background Neovascular age-related macular degeneration (AMD) is responsible for the majority of severe vision loss cases and is mainly caused by choroidal neovascularization (CNV). This condition persists or recurs in a subset of patients and regresses after 5 or more years of anti-vascular endothelial growth factor (VEGF) treatment. The precise mechanisms of CNV continue to be elucidated. According to our previous studies, macrophages play a critical role in CNV. Herein, we aimed to determine the morphological changes in macrophages in CNV to help us understand the dynamic changes. Methods Mice were subjected to laser injury to induce CNV, and lesion expansion and macrophage transformation were examined by immunofluorescence and confocal analysis. Several strategies were used to verify the dynamic changes in macrophages. Immunofluorescence and confocal assays were performed on choroidal flat mounts to evaluate the morphology and phenotype of macrophages in different CNV phases, and the results were further verified by western blotting and RT–PCR. Results The location of infiltrated macrophages changed after laser injury in the CNV mouse model, and macrophage morphology also dynamically changed. Branching macrophages gradually shifted to become round with the progression of CNV, which was certified to be an M2 phenotypic shift. Conclusions Dynamic changes in macrophage morphology were observed during CNV formation, and the round-shaped M2 phenotype could promote neovascularization. In general, the changes in morphology we observed in this study can help us to understand the critical role of macrophages in CNV progression and exploit a potential treatment option for CNV indicated by a shift in macrophage polarity.